Physical activity, sedentary behavior, and risk of sepsis: a two-sample mendelian randomization study - Zhang, Yang; Rong, Yu; Mao, Jun; Zhang, Jin; Xiao, Wenyan; Yang, Min (Frontiers in Medicine, 2024)
Objective This investigation aimed to explore the potential causal relationship between physical activity, sedentary behavior and the risk of sepsis. Methods Using a two-sample Mendelian randomization approach, this study evaluated the association between physical activity (including moderate to vigorous physical activity [MVPA], vigorous physical activity [VPA], and accelerometer assessed physical activity) and sedentary behaviors (including television watching, computer use, and driving) with the risk of sepsis. This assessment was based on whole-genome association study data from the UK Biobank and the FinnGen database. Causal inferences were estimated using inverse variance-weighted, weighted median, and MR-Egger methods. Sensitivity analyses were performed using Cochran’s Q test, the MR-Egger intercept test, and the leave-one-out method. Results The risk of sepsis was significantly inversely associated with genetically predicted MVPA (odds ratio [OR] 0.47, 95% confidence interval [CI] 0.24–0.93, P = 0.0296) and VPA alone (OR 0.19, 95% CI 0.04–0.87, P = 0.0324). Conversely, prolonged driving time showed a significant positive association with the risk of sepsis (OR 3.99, 95% CI 1.40–11.40, P = 0.0097). Conclusion This study provides preliminary evidence of a causal relationship between MVPA and VPA and a reduced risk of sepsis, while prolonged sedentary behaviors such as driving are positively associated with an increased risk of sepsis. These findings provided essential scientific evidence for the development of effective sepsis prevention strategies.